2019
DOI: 10.7150/ijbs.31583
|View full text |Cite
|
Sign up to set email alerts
|

5-aminolaevulinic acid-based photodynamic therapy inhibits ultraviolet B-induced skin photodamage

Abstract: To evaluate the photoprotective effect of 5-aminolaevulinic acid-based photodynamic therapy (ALA-PDT) on ultraviolet B (UVB)-induced skin photodamage. In vivo experiments, the dorsal skin of hairless mice were treated with ALA-PDT or saline-PDT, and then exposed to 180 mJ/m2 UVB. Results showed that the number of sunburn cells and apoptotic cells in the epidermis of ALA-PDT-treated groups at 24 h after UVB irradiation were significantly decreased compared with those in the UVB groups. And the removal rate of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Qiang et al (2016) found that cellular autophagy could promote the recognition of DNA damage by sensor proteins XPC and DDB2, as well as improve the clearance efficiency of CPDs and 6-4PPs. Our previous study also showed that low-dose ALA-PDT accelerated CPDs clearance (Hua et al, 2019). However, whether the autophagy induced by low-dose ALA-PDT reduces apoptosis of HaCaT cells by accelerating DNA repair remains to be further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…Qiang et al (2016) found that cellular autophagy could promote the recognition of DNA damage by sensor proteins XPC and DDB2, as well as improve the clearance efficiency of CPDs and 6-4PPs. Our previous study also showed that low-dose ALA-PDT accelerated CPDs clearance (Hua et al, 2019). However, whether the autophagy induced by low-dose ALA-PDT reduces apoptosis of HaCaT cells by accelerating DNA repair remains to be further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical studies found that if added with DNA‐repairing enzymes (photolyase and T4 endonuclease V), conventional sunscreen showed a stronger capacity to repair DNA and inhibit cell apoptosis, thus assisting in preventing photoaging 11 . Our previous research also revealed that low‐dose ALA‐PDT significantly increased the expression of proteins in DNA damage repair pathways and accelerated the clearance of DNA photoproducts induced by UV radiation in HDFs 12 . However, the precise mechanism by which low‐dose ALA‐PDT regulates the DNA damage repair pathways remains unknown.…”
Section: Introductionmentioning
confidence: 83%
“… 11 Our previous research also revealed that low‐dose ALA‐PDT significantly increased the expression of proteins in DNA damage repair pathways and accelerated the clearance of DNA photoproducts induced by UV radiation in HDFs. 12 However, the precise mechanism by which low‐dose ALA‐PDT regulates the DNA damage repair pathways remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bach2 knockdown with adenovirus induced cell senescence and Bach2 depletion with low‐level PDT treatment somewhat decreased SA‐β‐gal activity. Hua et al [37] evaluated the photoprotective effect of low‐dose ALA‐PDT on UVB‐induced skin photodamage. Results showed that in the BALB/c athymic nude mice, the number of sunburn cells and apoptotic cells in the epidermis of ALA‐PDT‐treated group (10% ALA +12 J/cm 2 red light +180 mJ/cm 2 UVB) at 24 h after UVB irradiation were essentially diminished compared with those in the UVB group (saline +180 mJ/cm 2 UVB).…”
Section: Low‐dose Ala/mal‐pdt In Skin Rejuvenationmentioning
confidence: 99%